Functional Properties and Applications of Egg White Protein Hydrolysates - Julmanlik, Tipwalee; Kongruang, Sasithorn (Journal of Food Technology, Siam University, 2019)
Protein hydrolysates are products derived from the hydrolysis of protein to gain different sizes of peptide and free amino acid. The production of protein hydrolysates involves either chemical hydrolysis using acid, alkaline or enzymatic hydrolysis through protease under the specific condition. The production of protein hydrolysate can be produced from many sources of protein. One of the most important source is the egg white protein which play a vital role in the food industry and popularly used as neutraceuticals. Moreover, it also contains many functional properties as emulsifier, foam stability and antioxidant. This source of hydrolysate is suitable for people who have a food restriction, need high protein content. It also can be used as bioactive substances for human health. This review article presents research and information related to egg white protein hydrolysate, the production process of egg white protein hydrolysate and the applications of egg white protein hydrolysates in the food and pharmaceutical industry.